UV-irradiation of skin enhances glycolytic flux in bone marrow-differentiated dendritic cells - Hart, P.; McGonigle, T.; Keane, K.; Newsholme, Philip; Ghaly, S.; Carter, K.; Anderson, D.; Scott, N.; Goodridge, H. (WILEY-BLACKWELL, 2016)
Following UV irradiation of skin, dendritic cells (DCs) differentiating from the bone marrow (BM) of mice have a reduced ability to prime new immune responses; their reduced immunogenicity is maintained for at least 16 weeks in UV-chimeric mice. We hypothesized that different metabolic states underpin changes in DC function. Compared with DCs from the BM of non-irradiated mice, DCs from the BM of UV-irradiated mice produced more lactate and utilized greater amounts of glucose, a profile that was supported by greater glycolytic flux when incubated in low-serum-containing medium. Responses to a mitochondrial stress test were similar suggesting that the DCs from the BM of UV- irradiated mice had not switched from a profile of oxidative phosphorylation, but were imprinted for greater glycolytic responses. After microarray profiling, RT-qPCR confirmation and Ingenuity pathway analysis, greater expression of the enzyme, 3-hydroxyanthranilate 3,4-dioxygenase, was identified as a potential contributor to increased glycolysis by BM-differentiated DCs. This enzyme provides the final step of the biosynthetic pathway from tryptophan to quinolinate, the universal de novo precursor to the pyridine ring of nicotinamide adenine dinucleotide (NAD), and may provide a mechanism to ensure sufficient NAD is available to support enhanced glycolysis. Increased lactate production was also measured for DCs from the BM of 16-week engrafted UV-chimeric mice and suggests long-lasting imprinting of progenitor cells for altered immunometabolism in their progeny cells. This study provides evidence of changes to metabolic states that associate with altered DC function.